Interaction Between Race and Gender and Effect on Implicit Racial Bias Against Blacks - Shervin Assari (International Journal of Epidemiologic Research, 2018)
Background and aims: Exposure and vulnerability to racial discrimination is not solely a function of race but the intersection of race and gender, with Black men experiencing more discrimination than Black women. This phenomenon is explained by the subordinate male target hypothesis, suggesting that majority of men specifically target men of color. If that is the case, implicit bias would be most common among the majority of men. The current cross-sectional study investigated race by gender differences in implicit bias against Blacks. Methods: Data came from Harvard University’s Project Implicit, an online survey, conducted during 2006-2016. Data included 444422 implicit association tests (IATs) which were taken by Blacks (n=56384) and Whites (n=388038). Using IAT, the dependent variable was implicit bias against Blacks. Independent variables were race, gender, and age. Using SPSS, linear regressions were utilized to test the additive and multiplicative effects of race and gender on implicit bias against Blacks. Results: Race (b = 0.39; 95% CI = 0.38-0.39) and gender (b = 0.05; 95% CI = 0.05-0.05) were associated with IAT score suggesting higher implicit bias against Blacks among Whites and men. A significant interaction was found between race and gender (b = 0.05; 95% CI = 0.04-0.07), suggesting the highest level of implicit bias against Blacks among White men. Conclusion: It is not solely race and gender but their intersection that shapes social distribution of implicit bias against Blacks. This finding extends the previous literature showing that not solely race or gender but their intersection influences exposure to discrimination.